Functional magnetic resonance imaging studies of acupuncture at ST36: a coordinate-based meta-analysis - Zhang, Jinhuan; Liu, Yongfeng; Li, Zihan; Hu, Qingmao; Huang, Xingxian; Lv, Hanqing; Xu, Jinping; Yu, Haibo (Frontiers in Neuroscience, 2023)
Background Functional magnetic resonance imaging (fMRI) has been widely used to investigate the brain effect of acupuncture point Stomach 36 (ST36, Zusanli). However, inconsistent results have hindered our understanding of the neural mechanisms of acupuncture at ST36. Objective To perform a meta-analysis of fMRI studies on acupuncture at ST36 to assess the brain atlas of acupuncture at ST36 from available studies. Method Based on a preregistered protocol in PROSPERO (CRD42019119553), a large set of databases was searched up to August 9, 2021, without language restrictions. Peak coordinates were extracted from clusters that showed significant signal differences before and after acupuncture treatment. A meta-analysis was performed using seed-based d mapping with permutation of subject images (SDM-PSI), a newly improved meta-analytic method. Results A total of 27 studies (27 ST36) were included. This meta-analysis found that ST36 could activate the left cerebellum, the bilateral Rolandic operculum, the right supramarginal gyrus, and the right cerebellum. Functional characterizations showed that acupuncture at ST36 was mainly associated with action and perception. Conclusion Our results provide a brain atlas for acupuncture at ST36, which, besides offering a better understanding of the underlying neural mechanisms, also provides the possibility of future precision therapies.